Correlation and path analysis in components of grain yield of cowpea genotypes - Almeida, Wener; Fernandes, Francisco Ronaldo; Teófilo, Elizita; Bertini, Cândida Hermínia (Revista Ciência Agronômica, 2014)
This study aimed at verifying the effect of genotype x environment interaction on the relative contribution of yield components and final production of different cowpea genotypes. For this, data of yield components of 22 cowpea genotypes were evaluated in four environments in the State of Ceará. A one-way ANOVA tested the variability between genotypes and the Scott-Knott test compared the mean values of the genotypes. The correlations were estimated by a path analysis. A differentiated response from the genotypes to each environment was observed for all traits examined, indicating the need to perform the test for each situation separately. The number of pods per plant is the yield component with great potential of genetic gain in additional cycles of selection of more productive genotypes. The number of pods per plant and the number of grains per pod were the yield components with greater direct effects on the productivity.